The impact of work engagement on turnover intention at Mannvit - Ragnheiður K Hjálmarsdóttir 1987- (2016)
It is extremely valuable for organizations to have employees who are engaged at work, both in terms of cost and performance. The objective of this study was to examine turnover intentions among employees at Mannvit in Iceland and explore how work engagement is related to those intentions, using Utrecht Work Engagement Scale (UWES-9) and Turnover Intention Scale (TIS-6). The main causes and consequences of engagement and turnover are discussed in the literature review chapter, as well as models that explain these processes. A quantitative study was conducted in March 2016 in the form of an online survey. A total of 132 employees at Mannvit participated in this study, aged 21 to 70, with 89.8% being male and 10.2% being female. The results indicated that a large portion of employees at Mannvit is engaged at work and that work engagement is significantly and negatively related to turnover intentions. These findings suggest that when employees experience high levels of work engagement, it is less likely that they have intentions to leave the organization. The results are consistent with findings of prior research. Keywords: Work engagement, turnover intention, engineering consulting.